2021
DOI: 10.1038/s41375-021-01347-6
|View full text |Cite
|
Sign up to set email alerts
|

Dual targeting of the DNA damage response pathway and BCL-2 in diffuse large B-cell lymphoma

Abstract: Standard chemotherapies for diffuse large B-cell lymphoma (DLBCL), based on the induction of exogenous DNA damage and oxidative stress, are often less effective in the presence of increased MYC and BCL-2 levels, especially in the case of double hit (DH) lymphomas harboring rearrangements of the MYC and BCL-2 oncogenes, which enrich for a patient’s population characterized by refractoriness to anthracycline-based chemotherapy. Here we hypothesized that adaptive mechanisms to MYC-induced replicative and oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
3
10
0
Order By: Relevance
“…To the best of our knowledge, this is the first study evaluating the presence of intrinsic DNA damage and basal DDR activation in preclinical models of TCL. This is not surprising, as similar evidence was already reported in solid tumors and in some hematological malignancies—namely, DLBCL, MM, AML, and CLL [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Of interest, in MM, Cottini and colleagues reported that DNA damage is caused by replicative stress and identified a subset of patients characterized by chromosomal instability and poor prognosis and correlated these features with an increased expression of the oncogene MYC [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study evaluating the presence of intrinsic DNA damage and basal DDR activation in preclinical models of TCL. This is not surprising, as similar evidence was already reported in solid tumors and in some hematological malignancies—namely, DLBCL, MM, AML, and CLL [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Of interest, in MM, Cottini and colleagues reported that DNA damage is caused by replicative stress and identified a subset of patients characterized by chromosomal instability and poor prognosis and correlated these features with an increased expression of the oncogene MYC [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 82%
“…In recent years, several efforts have been made by us and others to elucidate the genetic features of TCLs, reporting a broad range of copy number alterations (CNAs) and structural variations (SVs) rather than point mutations [ 6 , 7 , 8 ], thus suggesting that TCLs are characterized by genomic instability. It is well consolidated that genomic instability is a hallmark of cancer cells [ 9 , 10 , 11 ] that has been recently described also in hematological malignancies including multiple myeloma (MM), diffuse large B cell lymphoma (DLBCL), acute myeloid leukemia (AML), and chronic lymphocytic leukemia (CLL) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ] but has never been investigated in TCLs. A peculiarity of genomic instability is the presence of intrinsic DNA damage usually associated with basal activation of the DNA damage response (DDR).…”
Section: Introductionmentioning
confidence: 99%
“…The FISH assay was carried out with a Fluorescent in situ Hybridization Kit (RiboBio Co., Ltd.) in accordance with the instructions [ 28 ]. Briefly, after fixation, endothelial cells were treated with 0.5% Triton X-100, dehydrated, and hybridized with Alexa 488-labeled circUSP36 probes and Cy3-labeled miR-637 probes.…”
Section: Methodsmentioning
confidence: 99%
“…By blocking the mitochondrial pathway, BCL2 prevents apoptosis, and this protein is considered a target for future therapies. 35,36 Quinoxaline drug candidates XK469 and CQS exhibit antiproliferative and proapoptotic effects against cancers, including through the mitochondria. 37,38 In a recent work by Yukari Ono and colleagues, 38 quinoxaline-1,3,4-oxadiazole hybrid derivatives were considered as potential inhibitors of the antiapoptotic BCL2 protein.…”
Section: Assessment Of Apoptosismentioning
confidence: 99%